Anti-inflammatory and Anti-infertility Effects of Ethanol Extract of Turmeric (Curcuma longa) in Male Wistar Rats with Type 2 Diabetes Mellitus Induced by Streptozotocin-Nicotinamide-High Fat Diet - Vivian, Vivian; Lim, Hadyanto; Siahaan, Jekson Martiar; Anto, Endy Juli; Ilyas, Syaffrudin; Ardinata, Dedi (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a complex metabolic disorder associated with chronic inflammation and male reproductive dysfunction. The ethanol extract of turmeric (Curcuma longa) has demonstrated potential as an alternative therapeutic agent due to its anti-inflammatory and reproductive restorative properties. This study aims to analyze the anti-inflammatory and anti-infertility effects of the ethanol extract of Curcuma longa in male Wistar rats with T2DM induced by a streptozotocin-nicotinamide-high fat diet (STZ-NA-HFD). Subjects and Method: Thirty male Wistar rats were randomized into six groups (n=5): normal control (K1), diabetic control (K2), positive control (T2DM + metformin 45 mg/kgBW, K3), and three treatment groups receiving Curcuma longa extract at doses of 50 mg/kgBW (K4), 100 mg/kgBW (K5), and 150 mg/kgBW (K6). Diabetes was induced with STZ (55 mg/kgBW) and nicotinamide (120 mg/kgBW). Blood glucose, IL-6, testosterone levels, sperm count, and sperm motility were evaluated after 21 days of treatment. Results: The turmeric extract significantly reduced blood glucose levels (p<0.001) and IL-6 concentrations from 574.06±68.99 to 214.06±78.71 ng/mL at a dose of 150 mg/kgBW (p<0.001). Normal sperm motility increased significantly at 150 mg/kgBW (20.0±2.55%) compared to the diabetic control (8.40±2.07%) (p=0.008). Conclusion: The ethanol extract of Curcuma longa demonstrated significant anti-inflammatory activity by reducing IL-6 levels and improving glycemic control. Its anti-infertility effect was reflected by enhanced sperm motility, particularly at the 150 mg/kgBW dose. These findings indicate that Curcuma longa possesses potential as an adjuvant therapy for the management of T2DM and its associated complications.